The Effect of Stress Inoculation Program on the Quality of Life of Nurses Working in Psychiatric Wards - Mazlom RS; Darban F; Kashani‌Lotfabadi (Iran University of Medical Sciences, 2012)
Background & Aim: The multi dimensional construct of quality of life make it vulnerable to stress influence. Psychiatric Nurses experience high levels of occupational stress. So using preventive stress management programs would seem to be necessary. The aim of this study is to determine the effect of a Stress Inoculation Program on the quality of life of nurses working in psychiatric wards .   Material ;Methods: It was an experimental study with pre- post test design and control group. Sixty nurses and Healthcare workers, working in Ebne-Sina psychiatric hospital of Mashhad city were recruited and randomly assigned into two experimental (n=30) and control (n=30) groups. Quality of life questionnaire (SF-36) was used as data gathering scale in three stages (before intervention, at the end of second session and 1 month after intervention). The intervention included two sessions (each 8 hours) of stress Inoculation program that was carried out with a one weak interval. Data were analyzed by Kolmogrov-smirnov∞Shapiro-wilk, χ2, t, Repeated Measures and Fridman tests using SPSS-PC (v. 11.5).   Results: The findings revealed that the mean score of quality of life in experimental group in pre-intervention stage (89.2±11) have been increased to 97.4±11.1 after intervention and to 105±8.6 in the third stage (one month later) and it was significantly more than control group (P<.005). The quality of life of the control group significantly decreased in post intervention stage and one month later (P<.001). Conclusion: Regarding the effect of stress inoculation program on nurses' quality of life, using this approach is recommended to managers of psychiatric wards.